Golf-Stream: Swing motion analysis using multiple cameras and augmented reality techniques - Gerard, P.; Gagalowicz, A. (Expertise in Elite sport. 2nd International Days of Sport Sciences, 12.-15. November 2002, INSEP, Paris (France), 2002)
Introduction Augmented reality has already been used in sport broadcasting. It consists in overlaying graphics elements - speed data, swing plane - to the original video in order to offer richer and improved images to the TV audience, speakers in sport or sportive experts. We developed a new 3D tracking technique from image analysis using several synchronized video cameras and located directly on a golf field, in order to improve the content of golf tournament on TV. For some sports such as golf, motion capture in studio is not appropriate since the athlete adapts his play to the environment. This is the reason why developing a new motion capture system for outdoor purposes and without markers might be really useful. The GOLF-STREAM project provides data to better understand golf actions by presenting enhanced images, to better analyse and develop golf techniques, to coach and improve champion performances and to extract and visualise some pedagogical rules. The algorithm is a 3D articulated model-based tracker using a simplified anthropometric virtual 3D human. A generic model needs, at first, to be adjusted to the morphology to the filmed champion. An interactive positioning of the 3D model on the first frame of a video sequence is performed, then, the tracking algorithm automatically computes the evolution of the values of the set of degrees of freedom of the human body all along the swing motion.